CONSUMER BUYING PATTERNS IN THE AFFORDABLE HOUSING MARKET - Naik, Yash; Chavan, Vishal; Sharma, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
The affordable housing market in India has expanded rapidly over the last decade due to rising urbanization, government incentives, competitive pricing, and a shift in consumer financial behavior. This research paper examines the key factors influencing consumer buying patterns in the affordable housing segment, particularly among middle-income and lower-middle-income groups. The study is based entirely on secondary data, including academic research, industry reports, and government publications. The findings reveal that buyers prioritize affordability, financial security, location advantages, accessibility to essential amenities, and builder credibility. Digital information sources and post-pandemic behavioral shifts have also significantly impacted home-buying decisions. The study concludes that the affordable housing sector is driven by a mix of rational evaluation—such as budget constraints and loan eligibility— and emotional motivations such as security and long-term financial stability. Recommendations are provided to help developers and policymakers further enhance consumer confidence in this sector.